Computerized reading fluency assessment : task validity and the strongest discriminators of fluency skills among second-graders - Koikkalainen, Maija (2015)
This study examines how well computerized reading fluency assessment measures correspond to the more traditional pen-and-paper methods; and which computerized measures best discriminate between children poor reading fluency skills and the control group. The study was conducted in Finland among 203 second-graders, i.e. 7-8 year olds. The children were divided into two groups: the at-risk for reading difficulties group and control group, based on their standardized score on word-level fluency test. 36 of the participants placed in the ‘at-risk’ group, and 167 in the control group. On the course of the study, the participants conducted various tasks in a computerized, interactive GraphoGame learning environment, which recorded their results on the following measures: grapheme-phoneme correspondence, phonological awareness, phonological memory, phonemic length discrimination, short-term memory, rapid automatized naming, receptive vocabulary, word recognition, pseudo-word recognition, spelling, pseudoword spelling and sentence reading fluency (both large and normal letter spacing). They also took part in traditional pen-and-paper tests with the corresponding measures. Pearson correlations and logistic regression analysis were used to study the research questions. The results showed that majority of the computerized measures compared to the traditional measures well. Sentence reading with large letter spacing, word recognition accuracy and rapid automatized naming were found as the strongest discriminators of reading fluency skills between the two groups. The results shed positive light on using computerized methods in reading assessment.